The results of the radiotherapy of brain metastases of non-small-cell lung cancer - Brzozowska, Anna; Grzybowska, Ludmiła; Mazurkiewicz, Maria (Contemporary Oncology/Współczesna Onkologia, 2001)
A group of 50 patients with brain metastases of non-small-cell lung cancer (NSCLC) was reviewed. Among 24 of them brain metastases were the first symptoms of NSCLC. All patients underwent radiotherapy in the form of a whole-brain irradiation. The influence of some prognostic factors such as: age, gender, multiplicity of brain metastases, hystological subtype and interval between diagnosis of NSCLC and brain metastases on survival time was estimated. Median survival time calculated from the end of radiotherapy of brain metastases was 4,42 months. There was no statistically significant correlation between the median survival time and prognostic factors analyzed. It is reasonable to search other prognostic factors, which can be helpful to identify the group of patients with brain metastases from NSCLC, who will have survival benefit after the brain irradiation.